Avaliação do acometimento por COVID-19 dos trabalhadores dos serviços assistenciais de saúde, em seus ambientes de trabalho, no período de março de 2020 a maio de 2021, em Minas Gerais - Eleonora Assunção Morad Arantes (2022)
The illness of health professionals is especially worrying because, in addition to the repercussions related to the damage to the health and well-being of workers, which in itself is a reason for the concern of health authorities in the sense of adopting measures to prevent and control risks, it can also abruptly reduce human resources and compromise the quality and response potential of health services. The general objective was to evaluate the involvement by COVID-19 of workers in health care services, from March 2020 to May 2021, in Minas Gerais. Methodologically, it was a descriptive cross-sectional study, based on the analysis of secondary data from the Work Accident forms with Exposure to Biological Material - COVID-19 from Sinan, from the Influenza Syndrome by COVID-19 forms, from the e-SUS and of the individual record sheets of Severe Acute Respiratory Syndrome, and deaths by COVID-19 from Sivep-Gripe. Descriptive analyzes were performed using frequency distribution tables and graphs, using the Statistical Package for Social Science (SPSS) version 19.0 software. Additionally, annual incidence and prevalence were calculated, with respective 95% confidence intervals and spatial analysis using thematic maps. We also compared the incidences of COVID-19, according to the data from the three systems, with the incidence in the general population of MG. A similarity was observed in the profile of health care service workers affected by COVID-19, comparing the notifications from Sinan, e-SUS/Sivep-Gripe: female gender; age group from 30 to 44 years; among workers in the nursing class, and in the administrative class, among support service workers, and evolution with a favorable outcome. The incidence curves of the three systems and of the general population of MG were also similar, with a pattern of descent from March to June 2020, and the first peak around July/August 2020. A new peak was observed in January 2020. 2021 in the curves in the e-SUS/Sivep Gripe and the general population of MG, differing from Sinan, which showed a progressive drop in notifications. According to Sinan, the highest prevalence in 2020 was in the macro-regions Leste and Vale do Aço and in the Regional Health Units (URS) Leopoldina and Governador Valadares, and according to e-SUS/Sivep-Gripe, they were in the macro-regions Jequitinhonha and Northeast and in the URS Governador Valadares and Coronel Fabriciano. In 2021, in Sinan, the macro-regions Leste and Jequitinhonha and URS Leopoldina and Governador Valadares, and in e-SUS/Sivep-Gripe, the macro-regions Nordeste and Jequitinhonha and URS Diamantina and Varginha. As a technical product, recommendations were made for municipal managers and the top managers of the Regional Health Units, in order to guarantee timely notifications and safe work environments and processes. This work can contribute to the knowledge of the SARS-CoV-2 contamination scenario of health care service workers, and prevention and control measures, both individual and collective, to be implemented. It is also an aid to extrapolation of factors that facilitate contamination of this working population by other respiratory viruses.